2016
DOI: 10.3390/polym8090317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermally Induced Degradation of Branched Polypropylene by Using Rheology and Different Constitutive Equations

Abstract: Abstract:In this work, virgin as well as thermally degraded branched polypropylenes were investigated by using rotational and Sentmanat extensional rheometers, gel permeation chromatography and different constitutive equations. Based on the obtained experimental data and theoretical analysis, it has been found that even if both chain scission and branching takes place during thermal degradation of the tested polypropylene, the melt strength (quantified via the level of extensional strain hardening) can increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…In the first step, deformation rate dependent 'steady state' uniaxial extensional viscosity data (taken from the transient viscosity data peaks for given deformation rates, [60] and [69])…”
Section: Analytical Approximation For Ni * Vs Experimental Datamentioning
confidence: 99%
“…In the first step, deformation rate dependent 'steady state' uniaxial extensional viscosity data (taken from the transient viscosity data peaks for given deformation rates, [60] and [69])…”
Section: Analytical Approximation For Ni * Vs Experimental Datamentioning
confidence: 99%
“…Recent studies on entangled linear polypropylene melts have shown a well-developed Newtonian regime occurs above 2 • 10 6 1/s, which is linearly dependant on molecular weight suggesting that polymer chains become fully disentangled in such a flow regime [11]. In order to understand the role of the chain branching and temperature on high shear rate dynamics of polypropylene melts, well characterized low molecular weight linear PP Borflow HL512FB (L-PP) [11] and high molecular weight branched PP Daploy WB180HMS (LCB-PP) [12], both produced by Borealis Polyolefine (Linz, Austria), have been used in this work. Polymer blends were prepared by adding 10, 20 and 30 wt% of LCB-PP to L-PP in a twin screw extruder.…”
mentioning
confidence: 99%
“…In this work, we used GNF constitutive equation, which belongs to a new family of models [68][69][70][71][72][73],…”
Section: Constitutive Equationmentioning
confidence: 99%
“…The models handle the differences between highextensional-rate uniaxial, planar and biaxial extensional viscosities compared to others, more advanced constitutive equations (including the molecular-based Pom-Pom model), which unrealistically predict steady-state uniaxial and planar extensional viscosities virtually identical at high extensional strain rates [19,68,74]. These types of GNF models have been successfully tested for polymer melts with linear (mLLDPE [68,71], HDPE [68,69]) and differently branched structures (mLLDPE [68,69,71], mHDPE [68], LDPE [68][69][70]72]) including polymers with star type of the branching (LCB-PP [73]) using steadystate extensional viscosities measured at extensional strain rates typically up to about 10 s -1 , (i.e. at low Wi, where entanglements dominate the dynamics).…”
Section: Constitutive Equationmentioning
confidence: 99%